Redesign UI/UX Perpustakaan Digital UNRI Berbasis Mobile Dengan Fitur Auto Layout Menggunakan Metode Five Planes - novriandhandy; Unang Rio; Karpen; T. Sy. Eiva Fatdha (BETRIK, 2025)
The rapid development of digital technology has increased the demand for high-quality user interface (UI) and user experience (UX) design in online services, including the Riau University (UNRI) Digital Library, which has been available since 2016 as an academic resource platform. An evaluation using the User Experience Questionnaire (UEQ) revealed weaknesses in attractiveness and novelty, which reduced user satisfaction. This study aims to redesign the UI/UX of the UNRI Digital Library mobile application by applying the auto layout feature in Figma with the Five Planes framework (strategy, scope, structure, skeleton, surface). The research employed a mixed approach, including literature study, interviews with the library administrator, and UEQ surveys distributed to 100 active students as primary users. The redesigned prototype was evaluated with UEQ, and the results indicated improvement across all dimensions, particularly in attractiveness and novelty, which previously scored negative. The integration of auto layout enhanced design efficiency and consistency. The findings demonstrate that applying the Five Planes method supported by responsive design features can produce a more modern, intuitive, and engaging interface. This study provides practical implications for the development of digital library systems and theoretical contributions to mobile-based UI/UX design research.